Taking control of one's everyday life - a qualitative study of experiences described by participants in an occupational intervention - Louise Karlsson; Lena-Karin Erlandsson; Anna Cregård; Lena Nordgren; Marie Lydell (BMC, 2023)
Abstract Background Sick leave due to stress-related ill-health is increasing and is often caused by occupational imbalance. These types of issues tend to affect both the ability to work and cope with everyday life, as well as the overall experience of health, negatively. There is still little knowledge on how to prepare people and workplaces for the return-to-work process after participation in a work rehabilitation program due to stress and occupational ill-health. Therefore, this study aimed to describe what is needed to achieve a balanced everyday life that includes paid work as experienced by individuals who had participated in a ReDO® intervention due to occupational imbalance and ill-health. Methods The concluding notes from 54 informants' medical records were used for qualitative content analysis. The informants had participated in an occupational therapy group intervention to promote occupational health and regain full work capacity. Results The analysis resulted in one major theme and four categories describing how the informants perceive that they must take control of their everyday life as a whole. By doing so, they need to work with structurization and prioritization, social interaction, boundary setting, and occupational meaningfulness. Conclusion The study indicates a highly relational process, where it is impossible to divide life into private and work, and presupposes balance in everyday life in multiple dimensions. Its contribution includes the formulation of perceived needs in the transition between intervention and return to work and could, through further research, be used to generate a more effective and sustainable return- and rehabilitation models.